2022
DOI: 10.3390/ijms232315330
|View full text |Cite
|
Sign up to set email alerts
|

The PI3K/Akt Pathway in Meta-Inflammation

Abstract: Obesity is a global epidemic representing a serious public health burden as it is a major risk factor for the development of cardiovascular disease, stroke and all-cause mortality. Chronic low-grade systemic inflammation, also known as meta-inflammation, is thought to underly obesity’s negative health consequences, which include insulin resistance and the development of type 2 diabetes. Meta-inflammation is characterized by the accumulation of immune cells in adipose tissue, a deregulation in the synthesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(32 citation statements)
references
References 131 publications
0
32
0
Order By: Relevance
“…Since the obesity-associated oxidative stress contributes to the development of the characteristic subclinical inflammatory response, the expression of different proinflammatory markers was determined in fat and liver tissues. In epididymal fat, the expression levels of p38, AKT and COX-2 were determined, being these proteins closely related to the inflammatory response that occurs in obesity [ 28 , 29 , 30 ]. While metformin administration promoted a significant reduction in protein levels for MAPK and AKT, the extract showed a trend to reduce them, showing no statistical differences when compared to non-obese mice ( Figure 5 B,C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the obesity-associated oxidative stress contributes to the development of the characteristic subclinical inflammatory response, the expression of different proinflammatory markers was determined in fat and liver tissues. In epididymal fat, the expression levels of p38, AKT and COX-2 were determined, being these proteins closely related to the inflammatory response that occurs in obesity [ 28 , 29 , 30 ]. While metformin administration promoted a significant reduction in protein levels for MAPK and AKT, the extract showed a trend to reduce them, showing no statistical differences when compared to non-obese mice ( Figure 5 B,C).…”
Section: Resultsmentioning
confidence: 99%
“…In adipose tissue, the activation of this signaling cascade results in the promotion of lipid biosynthesis and the suppression of lipolysis. Therefore, activated AKT contributes to an increase in fat deposits [ 29 ]. Additionally, it has been reported that insulin resistance may result in overactivation of the PI3K/AKT pathway [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other diseases, such as pancreatic cancer, the PI3K/Akt axis is the upstream signaling pathway through which evodiamine modulates cellular activity [ 43 ]. Moreover, studies have also confirmed that the PI3K/Akt axis is involved in the regulation of inflammatory response and oxidative stress [ 44 , 45 , 46 ]. Following evodiamine treatment, p-PI3K and p-Akt protein levels decreased in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Direct actions of leptin on cell metabolism are rather unusual, and are mainly mediated by its effects on insulin sensitivity in adipocytes [ 8 ]. We found a reduction in the phosphorylation of the insulin receptor and downstream targets of this pathway in the epididymal fat of pair-fed and leptin-infused rats, which was more significant in the latter group, and this inhibited insulin’s actions in adipocytes [ 44 ]. In addition, JNK activation in leptin-infused rats could interfere with insulin signaling by increasing IRS1 degradation and triggering IRS1 serine phosphorylation in fat, thus lessening the signaling and promoting inflammation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%